2015
DOI: 10.1016/j.bbrc.2015.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Staphylococcus aureus exfoliative toxin D-like protein: Structural basis for the high specificity of exfoliative toxins

Abstract: Exfoliative toxins are serine proteases secreted by Staphylococcus aureus that are associated with toxin-mediated staphylococcal syndromes. To date, four different serotypes of exfoliative toxins have been identified and 3 of them (ETA, ETB, and ETD) are linked to human infection. Among these toxins, only the ETD structure remained unknown, limiting our understanding of the structural determinants for the functional differentiation between these toxins. We recently identified an ETD-like protein associated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Udder cleft dermatitis is a pathology lacking a clear etiology, but one of the bacterial inducers can be S. aureus. Moreover, some cases of sheep mastitis have been associated with the exfoliative toxin D-like protein (42).…”
Section: Discussionmentioning
confidence: 99%
“…Udder cleft dermatitis is a pathology lacking a clear etiology, but one of the bacterial inducers can be S. aureus. Moreover, some cases of sheep mastitis have been associated with the exfoliative toxin D-like protein (42).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of ETA was the first to be determined in atomic detail [51], followed by ETB [52] and by ETD [24] and currently, the atomic coordinates of six ET structures have been deposited with the Protein Data Bank (www.rcsb.org). The crystallographic structures of ETs have revealed much about their mechanisms of action, lack of hydrolytic activity against substrates in the native state, and the susceptibility of certain constituent layers of the epidermis to disruption by ETs.…”
Section: Structural Biology and Mechanism Of Exfoliative Toxinsmentioning
confidence: 99%
“…In 2002, a new exfoliative toxin (ETD) was identified in a clinical sample of S. aureus [13]. Recent crystallographic studies indicated that the ETD-like protein isolated from ewe mastitis [23] is structurally homologous to ETA and ETB [24]. ETA is codified by the eta gene on chromosomal DNA, carried on the genome on a temperate phage, and ETB by the etb gene on a large plasmid DNA [22,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we were able to characterize a new S. aureus ET that had initially been identified in S. aureus strains associated with mild mastitis in ewes 7 . It was previously named ETD-like protein because its predicted protein sequence determined from the O46 genome sequence displayed 59% identity with the ETD protein 7,9 . It also significantly differed from the other well-characterized ETA and ETB.…”
Section: Discussionmentioning
confidence: 99%
“…Of note was the fact that it harbored the typical catalytic site encountered in the other ET proteins described to date. This protein was tentatively referred to as an ETD-like protein, and its crystal structure was determined 9 .…”
Section: Introductionmentioning
confidence: 99%